An acoustic exploration of event construals in Bengali language. Issue 1 (April 2021) - Chowdhury, S; Gayen, P K; Sarkar, U; Banerjee, A; Sanyal, S; Karmakar, S; Ghosh, D
Abstract: The world is full of events, and events are construed. One of the major research questions, therefore, seeks to understand the way events are construed through language. Event construals involve the syntacto-semantic properties of certain linguistic categories such as Verb, Tense, Aspect, Modality, etc. Serial Verb Constructions (SVC) and Complex Predicate Constructions (CPC) are no exception to this very fact. In this work, we look forward to compare both linear and non linear acoustical features generated from SVC and CPC events found in sentences of Bengali language. For this, we recorded 60 common utterances of Bengali language containing SVC and CPC events individually (around 36 of them belong to SV category while the rest belong to CP category), from 1 male and 1 female native Bengali speakers. The serial verb construction in these utterances may contain two (2) serial verbs in either simultaneous or sequential order, while few sentences are such that they can be interpreted both as SV or CP events. The main objective is to look for robust acoustic features which lead to perceptual categorization of events as SV or CP with a particular linguistic background. Various linear features like MFCC (Mel frequency Cepstral Coefficients), spectral skewness/energy, pause duration, pitch profile and nonlinear features like Fractal Dimension (FD) have been employed for the classification purpose. This work is a pilot study of an ongoing project which looks to explore the concept integrating capacity of human brain in terms of Syntactic Compositionality or Semantic Combinatorics in a complex sentence. This preliminary acoustic study reveals interesting new results in terms of perceptual linguistic representation of the event construals.